General Introduction - Dijkstra, Jitse H. F.; Raschle, Christian R. (Religious Violence in the Ancient World: From Classical Athens to Late Antiquity, 2020)

Religious Violence in the Ancient World: From Classical Athens to Late Antiquity - Dijkstra, Jitse H. F.; Raschle, Christian R. (Cambridge University Press, 2020)

The Expulsion of Isis Worshippers and Astrologers from Rome in the Late Republic and Early Empire - Raschle, Christian R. (Religious Violence in the Ancient World: From Classical Athens to Late Antiquity, 2020)
Recent debates on religious violence in the Roman empire have focused mainly on the change from a polytheistic to a monotheistic empire, ‘das Problem des Monotheismus’, as stated by the Egyptologist Jan Assmann. In the tradition of the Enlightenment, polytheism and traditional religious practices are depicted as tolerant, because their inclusive character allowed individuals to adhere freely to as many and whichever cults they desired. The associated belief-systems are generally considered to have been open and non-coercive. Even the very category of ‘belief’ has been called into question, since it was the adequate performance of the rites that mattered. New cults could always be adapted and reinterpreted in familiar terms. Since gods and spirits were conceived of mainly as local entities, the veneration of foreign gods and spirits in a foreign country would be nothing more than a polite act: when in Alexandria, do as the Alexandrians do. Finally, nothing prevented an individual with enough backers and financial means from founding his or her own shrine.